The surface organization of diacylglycerol pyrophosphate and its interaction with phosphatidic acid at the air-water interface - Villasuso, Ana Laura (2010)
Diacylglycerol pyrophosphate (DGPP), a phosphorylated form of phosphatidic acid (PA), gained attention recently due to its role as signaling lipid. However, little is known about its surface organization and potential impact on membrane-mediated function. In this work we investigated the interfacial behavior of Langmuir monolayers formed with pure DGPP and of its mixtures with PA. We found that changes of the subphase pH affect the surface behavior of DGPP. At pH 8, DGPP forms liquid expanded monolayers with a compressibility modulus of about 60 mN m−1 at collapse. On acidic solutions, the compressibility modulus increases to 90 mN m−1 and the average molecular area is smaller. At pH 8, DGPP and its precursor PA form thermodynamically favored topographically homogeneous non-ideal mixtures. The interaction among these lipids leads to a non-ideal diminution of the mean molecular area and consequently, to an increase of the compressibility modulus, with variations of the surface electrostatics. The favorable interaction of PA and DGPP, leading to changes of the film packing suggest that DGPP may act as a structural signal transducer in membrane-mediated cellular processes.